2011
DOI: 10.1016/j.appet.2011.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Project TwEATs. A feasibility study testing the use of automated text messaging to monitor appetite ratings in a free-living population

Abstract: There are no standardized methods for monitoring appetite in free-living populations. Fifteen participants tested a computer-automated text-messaging system designed to track hunger ratings over seven days. Participants were sent text-messages (SMS) hourly and instructed to reply during waking hours with their current hunger rating. Of 168 SMS, 0.6-7.1% were undelivered, varying by mobile service provider, On average 12 SMS responses were received daily with minor variations by observation day or day of the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…We are confident in the quality of our data particularly due to the relatively low burden, low recall bias, and frequency of prompts. Another strength of this study is the automated text-messaging system designed specifically for Project TwEATs (Schembre & Yuen, 2011). The system, which was supported by social media websites, utilized the participants’ own mobile phones and service plans, which drastically reduced the cost burden that can be associated with EMA data collection methods that require application programming on specified platforms that quickly become obsolete due to the high-speed pace of technological advancements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are confident in the quality of our data particularly due to the relatively low burden, low recall bias, and frequency of prompts. Another strength of this study is the automated text-messaging system designed specifically for Project TwEATs (Schembre & Yuen, 2011). The system, which was supported by social media websites, utilized the participants’ own mobile phones and service plans, which drastically reduced the cost burden that can be associated with EMA data collection methods that require application programming on specified platforms that quickly become obsolete due to the high-speed pace of technological advancements.…”
Section: Discussionmentioning
confidence: 99%
“…Results from Project TwEATs I demonstrated that automated text-messaging is an acceptable method to monitor perceived hunger ratings in a sample of adults over a consecutive week (Schembre & Yuen, 2011) representing an improvement over previously validated methodologies (Almiron-Roig et al, 2009; Mattes, Hollis, Hayes, & Stunkard, 2005; Stratton et al, 1998; Stubbs et al, 2000; Yeomans, Gray, Mitchell, & True, 1997). For Project TwEATs II we recruited a new sample of participants to explore the relationships between perceived psychological and physiological states, and eating behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have also reported success with mobile technology-based interventions (120)(121)(122)(123)(124). Text messaging, in particular, has been used in a variety of behavioral intervention studies to provide reminders, cues, and positive reinforcement and enhance self-monitoring (125)(126)(127)(128).…”
Section: Population-based Nutrition Interventions In College Studentsmentioning
confidence: 95%
“…Food craving is also short lived (Werthmann, Roefs, Nederkoorn, Mogg, Bradley, & Jansen, 2011), making response latency an important consideration in this area. Preliminary evidence suggests that EMA via electronic devices, and particularly text messaging, is feasible for assessing appetite and food intake (Schembre & Yuen, 2011), and even among children (Shapiro, Bauer, Hamer, Kordy, Ward, & Bulik, 2008). Building on this, a number of pilot studies have begun to test the efficacy of weight loss and other dietary interventions based on text messaging, generally with encouraging results (Cole-Lewis & Kershaw, 2010; Gerber, Stolley, Thompson, Sharp, & Fitzgibbon, 2009; Napolitano, Hayes, Bennett, Ives, & Foster, 2012; Patrick, Raab, Adams, Dillon, Zabinski, Rock, et al, 2009).…”
mentioning
confidence: 99%